The role of relaxin family receptor 1 and 2 (RXFP1 and RXFP2) in gender- specific physiology and pathology - Alhujaili, Waleed (2021)
In most female mammals the peptide hormone relaxin plays an important role in reproductive physiologies, such as decidualisation, lactation, implantation, birth, uterine vascularization, and uterine quiescence, as well as maintaining systemic osmolarity during pregnancy. Both relaxin and the structurally related hormone INSL3 (insulin-like peptide 3) are specific ligands for the large GPCR receptors RXFP1 and RXFP2, respectively. At a low physiological nanomolar range, both peptide hormones can bind and activate only their cognate receptors, though in humans, relaxin may interact with RXFP2 at the high supra-physiological concentration.